Feasibility study and optimal coal drawing process for fully mechanized caving in close-distance extra-thick coal seams - ZHANG Wei; GAO Peng; CUI Bo; Asihaer·Niyazibieke; PAN Weidong (Gong-kuang zidonghua)
Research on optimal coal drawing parameters for working faces with significant variation in seam thickness, where the thickness exceeds the standard mining height in close-distance coal seams, has been limited. This study focused on the feasibility and optimal coal drawing process for fully mechanized caving in the 011N1−1 working face of the Xilutian Coal Mine, Pingzhuang Coal Industry (Group) Co., Ltd., Inner Mongolia. First, theoretical analysis determined that the maximum damage depth of the floor caused by mining in the overlying 021N2 working face was 3.88 m, which was less than the distance between the 011N1−1 and 021N2 working faces. This finding confirmed the feasibility of fully mechanized caving for the underlying 011N1−1 working face. Subsequently, using a combination of theoretical analysis and field measurements, the study employed a fuzzy mathematics method to quantify the effects of uniaxial compressive strength, seam burial depth, seam thickness, coal fracture development, roof grade, and interlayer gangue thickness on the caving characteristics of the top coal. Membership function evaluation indicated that the top coal caving tendency of the 011N1−1 working face were at a moderate level. Finally, a coal drawing numerical model was established using the PFC 2D discrete element particle flow software to analyze the effects of different cutting-to-drawing ratios and coal drawing methods on the recovery rate of the top coal. The results revealed that, when the seam thickness exceeded the standard mining height, setting the cutting-to-drawing ratio to 1∶4.5 effectively accommodated thickness variations with minimal impact on top coal recovery. Moreover, a three-cycle coal drawing process significantly improved the recovery rate. Field observations demonstrated that, after optimizing the coal drawing process, increasing the instantaneous cutting-to-drawing ratio with seam thickness better adapted to geological conditions and significantly enhanced top coal recovery in the working face.